Correlation of cognitive impairment with Mediterranean diet and mortality: a prospective cohort study - Ling Li; Xiaoxiao Zheng; Hongyue Ma; Mingxia Zhu; Xiuli Li; Xinhong Feng (Frontiers in Aging Neuroscience)
Background and aimLong-term adherence to the Mediterranean Diet has been shown to improve cognitive function in patients. However, there is a lack of evidence regarding the impact of the Mediterranean diet and cognitive impairment on long-term mortality outcomes. This study aims to explore whether there is an interaction between the degree of adherence to the Mediterranean diet and cognitive impairment on long-term mortality outcomes.MethodsThe study included 2,520 participants from the National Health and Nutrition Examination Survey (NHANES) conducted between 2011 and 2014. The adherence to the Mediterranean diet was assessed using the 9-point alternative Mediterranean diet index (aMED index). Cognitive function was assessed using the Consortium to Establish a Registry for Alzheimer’s disease (CERAD), the Animal Fluency Test (AFT), and the Digital Symbol Substitution Test (DSST). By accessing public records from the National Death Index (NDI), NHANES participants’ information was linked to death certificate records to determine mortality and causes of death during the follow-up period, up to December 31, 2019, with causes specified according to ICD-10. Participants were categorized based on the median aMED score into low adherence (scores 0–3), moderate adherence (score 4), and high adherence (scores 5–9) groups. Cognitive impairment was assessed by calculating the arithmetic mean of standardized scores (Z-scores) for each cognitive test. Participants with scores below the first quartile of the arithmetic mean were considered to have cognitive impairment. Cox proportional hazards regression models were used to assess the relationship between cognitive impairment, aMED, and all-cause and cardiovascular mortality outcomes. Additionally, the interaction between cognitive impairment and aMED on these outcomes was evaluated.ResultsThe study included 2,520 participants, with 481 deaths during the follow-up period, of which 129 (26.8%) were cardiovascular-related. The median aMED score in the population was 4, and 632 individuals (25.1%) were considered to have cognitive impairment. A higher aMED score was associated with a reduced risk of long-term all-cause mortality and cardiovascular-related mortality (HR, 0.65; 95% CI, 0.52–0.81, p < 0.001; HR, 0.73; 95% CI, 0.47–0.91, p = 0.039). Cognitive impairment was associated with an increased risk of long-term all-cause mortality and cardiovascular mortality (HR, 1.78; 95% CI, 1.46–2.18, p < 0.001; HR, 1.80; 95% CI, 1.22–2.64, p = 0.003). Individuals with both lower aMED scores and cognitive impairment had higher risks of all-cause and cardiovascular mortality. Subgroup analysis indicates that only in the cognitive impairment subgroup is a higher Mediterranean diet score associated with a reduced risk of cardiovascular mortality. There is an interaction between lower aMED scores and cognitive impairment in increasing cardiovascular-related mortality (p for interaction = 0.028).ConclusionThere is an interaction between adherence to the Mediterranean diet and cognitive impairment concerning cardiovascular-related mortality, but not all-cause mortality. Among individuals with cognitive impairment, adherence to the Mediterranean diet has a more significant impact on cardiovascular-related mortality.